The Influence of Manager Features in the Success of Project Management - Noro, Greice De Bem (2013)
Project management has emerged among current management models and has become a factor to create a competitive advantage for companies in relation to their competitors. However, despite the increased interest in project management, little has been explored regarding managers who work with this type of management and their influence on determining the success or failure of the business. In this context, the present study aimed to analyze the influence of the project manager for small and large businesses in Santa Maria/RS in relation to the success of the businesses. This research is classified as quantitative and descriptive because it was conducted through a field study based on an accessible sample of small and large businesses in the city of Santa Maria. The main results showed that the managers of the surveyed companies were in the intermediate level of development with regard to the success of the projects as proposed by Newton (2011). This factor, however, does not significantly influence the success of projects managed by them.